(untitled) (Research, Society and Development, 2022)
The objective of this study was to elaborate a blended hamburger with rosemary as a substitute for synthetic antioxidants and to evaluate the physicochemical characteristics and oxidation during 120 days of storage. The burgers were prepared using beef cutlets and chicken breast fillets in an entirely randomized design. It was considered as treatment the replacement (w/w) of the synthetic antioxidant by rosemary. The quality of the hamburger was evaluated from the physical-chemical parameters of oxidation by the TBARS method, color parameters (L*, a*, b*), and pH of the hamburgers under storage for 30, 45, 60, 90 and 120 days. The compounds camphor, 1,8-cineole and α-pinene were the majority in the essential oil identified by GC/MS and RAMAN spectroscopy. In the analysis of total antioxidant activity the essential oil showed lower activity (38%) than the hydroalcoholic extract (93.8%), both for concentrations of 100µg/mL. At 30 days of storage, there was no difference in luminosity between treatments (p>0.05), indicating that the addition of the aromatic herb did not influence this parameter. The quantification of the malonic dialdehyde content (mg of MDA/kg of sample) indicated that the treatments that used fresh or dried aromatic herb presented lower values (p<0.05) of the compounds from the oxidation, being statistically equal to the treatment with sodium erythorbate. The addition of rosemary in the meat product, both in the form of fresh herb and dried herb, in the presented level replaces the antioxidant sodium erythorbate, thus contributing to the provision of a product free of synthetic additive.